Machine learning and knowledge discovery for engineering systems health management - Srivastava, Ashok N. 1969-; Han, Jiawei (CRC Press, 2012)
"Systems health is a broad multidisciplinary field of study that generates huge amounts of data and thus is an extremely appropriate forum in which to utilize machine learning and knowledge discovery techniques. This book explores the use of machine learning and knowledge discovery in systems health research. It covers data mining and text mining algorithms, anomaly detection, diagnostic and prognostic systems, and applications to engineering systems. Featuring contributions from leading experts, the book is the first to explore this emerging research area"--Provided by publisher
Keywords: System failures (Engineering) -- Prevention -- Data processing.; Machine learning.; elektronické knihy; electronic books